2020
DOI: 10.3892/mmr.2020.11426
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression levels of inflammatory cytokines and adhesion molecules in lipopolysaccharide‑induced acute inflammatory apoM‑/‑ mice

Abstract: Apolipoprotein M (apoM) may serve a protective role in the development of inflammation. Nuclear factor-κB (NF-κB) and its downstream factors (including a number of inflammatory cytokines and adhesion molecules) are essential for the regulation of inflammatory processes. In the present study, the importance of apoM in lipopolysaccharide (LPS)-induced acute inflammation and its potential underlying mechanisms, were investigated using an apoM-knockout mouse model. The levels of inducible nitric oxide synthase (iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Goto-Kakizaki rats, a non-obese, spontaneous model of diabetic rats display better insulin sensitivity when overexpressing Apom, concomitantly with an increased insulin secretion and glucose utilization [106]. Concordant results were obtained in Apom-deficient mice which present impaired insulin sensitivity, high plasma inflammatory markers such as IL-6 or IL-1β, and hepatic NF-κB [99,107]. Yao et al also recently demonstrated that APOM is expressed in murine and human macrophages, interacts with the scavenger receptor BI to promote cholesterol efflux from the phagocytic cells and protects against atherosclerosis [108,109].…”
Section: Apommentioning
confidence: 88%
“…Goto-Kakizaki rats, a non-obese, spontaneous model of diabetic rats display better insulin sensitivity when overexpressing Apom, concomitantly with an increased insulin secretion and glucose utilization [106]. Concordant results were obtained in Apom-deficient mice which present impaired insulin sensitivity, high plasma inflammatory markers such as IL-6 or IL-1β, and hepatic NF-κB [99,107]. Yao et al also recently demonstrated that APOM is expressed in murine and human macrophages, interacts with the scavenger receptor BI to promote cholesterol efflux from the phagocytic cells and protects against atherosclerosis [108,109].…”
Section: Apommentioning
confidence: 88%
“…For instances, APOM could repress oxidized low‐density lipoprotein (ox‐LDL) ‐induced inflammation, thereby protecting the vascular endothelium (Zheng et al, 2019). It has been demonstrated that the levels of inflammatory cytokines are elevated in LPS‐induced APOM‐knockout mouse model (Shi et al, 2020). Besides, compelling evidence indicate that APOM deletion induces apoptosis in mouse kidney (Pei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NO is a small molecule synthesized by NOS named neuronal NOS (nNOS) and endothelial (eNOS), which are constitutive isoforms, and the iNOS that is negligible in resting cells but is induced by inflammatory cytokines and LPS [358,359,362,367,368]. LPS binds to the TLR4 on the surface of macrophage membranes, leading to the activation of MAPK or NF-κB signaling pathways and further iNOS gene expression [369] to produce NO. Additionally, microglia can exhibit a pro-inflammatory phenotype by LPS contributing to the activation of iNOS.…”
Section: Melatonin Inos and Calcium/calmodulinmentioning
confidence: 99%